2022
DOI: 10.2196/32234
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecosystem Therapeutic-2 Intervention in People With Major Depressive Disorder and Generalized Anxiety Disorder: Phase 1, Open-Label Study

Abstract: Background Recent studies have investigated the potential of treatments that modify the gut microbiome, such as fecal microbiota transplantation and probiotics, in individuals with psychiatric illnesses. Objective The aim of this study was to investigate the safety, tolerability, and efficacy of a novel gut microbiome therapeutic, Microbial Ecosystem Therapuetic-2 (MET-2), in people with depression and anxiety. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…There is some evidence that individuals with depression represent a population with specific bacterial enterotypes or have a reduction in the diversity of the gut microbiome [ 94 , 95 ]. Although some studies targeting the microbiome adopt methods such as probiotic supplementation or fecal transplant, diet manipulation may also be a safe and affordable way to change the microbiome [ 96 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that individuals with depression represent a population with specific bacterial enterotypes or have a reduction in the diversity of the gut microbiome [ 94 , 95 ]. Although some studies targeting the microbiome adopt methods such as probiotic supplementation or fecal transplant, diet manipulation may also be a safe and affordable way to change the microbiome [ 96 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of Lactobacillus plantarum PS128 led to a significant remission in depressive symptoms of MDD patients [115,116] . Furthermore, the encapsulated microbial therapeutic MET-2, which contains 40 strains of bacteria, was effective in reducing the mean Montgomery–Åsberg Depression Rating Scale and Generalized Anxiety Disorder-7 scores in MDD patients [117] …”
Section: Gut Microbiota and Neurological Diseasesmentioning
confidence: 99%
“…[115,116] Furthermore, the encapsulated microbial therapeutic MET-2, which contains 40 strains of bacteria, was effective in reducing the mean Montgomery-Åsberg Depression Rating Scale and Generalized Anxiety Disorder-7 scores in MDD patients. [117] Previous studies have found that gut microbiota dysbiosis may participate in the pathogenesis of MDD by regulating multiple molecular metabolic pathways, e.g., carbohydrate, GABA, phenylalanine, and tryptophan. [24,114] Clinicallybased findings provide good evidence for MDD analysis; however, clinical samples are susceptible to confounding factors, such as drugs, diet, and geography.…”
Section: ≥2mentioning
confidence: 99%
See 1 more Smart Citation
“…There is pre-clinical evidence to suggest that a vagotomy can inhibit depressive symptoms in rats, even after an FMT from an individual with depression-associated GM (Chinna et al, 2022; Kuijer et al, 2023; Liu et al, 2023; Rutsch et al, 2020; Wang et al, 2020a, 2020b). This supports the hypothesis that the vagus nerve exerts its effects via the MGBA and that it is necessary for the axis to function normally.…”
Section: Faecal Microbiota Transplantmentioning
confidence: 99%